2003
DOI: 10.1002/cncr.11763
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recurrent oral squamous cell carcinoma by [18F]‐2‐fluorodeoxyglucose‐positron emission tomography

Abstract: The morphologies of the fracture surface under impact and flexural testing of Mg(OH)2/Polypropylene (PP) composites and their modified composites were investigated by scanning electron microscopy. Experimental results indicated that addition of functionalized polypropylene (FPP) and acrylic acid (AA) and the formation of in situ FPP changed the fracture morphologies of Mg(OH)2/PP composites. We believe that addition of these modifiers improved the interfacial interaction and enhanced the interface adhesion bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Moreover, locoregional recurrences, after combined therapeutic modalities including conservative surgery, usually occur later. 18 F-FDG PET performed as a sequential investigation 4 mo after treatment, independent of whether recurrence is suggested, showed high accuracy (12,14,21,22). However, recurrences could also be apparent clinically or radiographically at the time of PET.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, locoregional recurrences, after combined therapeutic modalities including conservative surgery, usually occur later. 18 F-FDG PET performed as a sequential investigation 4 mo after treatment, independent of whether recurrence is suggested, showed high accuracy (12,14,21,22). However, recurrences could also be apparent clinically or radiographically at the time of PET.…”
Section: Discussionmentioning
confidence: 95%
“…[19][20][21][22] An SUV after therapy of more than 3 23,24 or 4 25 mg/mL is regarded as positive for a recurrent tumor. In our series, 4 patients underwent a PET/CT examination, and all 4 studies were suspicious for a recurrent tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms are defects in the antigen processing machinery 32,33 or increased expression of inhibitory molecules on tumor cells. 34 As several studies have demonstrated that upregulation of LDHA and GLUT-1 is related to a more aggressive phenotype and poor prognosis [35][36][37] the aim of our study was to investigate a possible link between an altered glucose metabolism and T cell infiltration and activation in RCC. Our results suggest that glucose metabolism has an impact on TIL and may be involved in the modulation of immune responses in the tumor environment.…”
mentioning
confidence: 99%